Researching Daily Life: becoming-philosophy and becoming- art in science - Maria da Conceição Silva Soares (Universidade Federal do Rio Grande do Sul, 2013)
In this text I argue that the trend in research being consolidated in Brazil as research on/of/with daily life shows the crossing of becoming-philosophy and becoming-art upon education science. With this purpose, I lay out a path for reflection consisting of an articulation of ideas defended by Deleuze and Guattari on philosophy, science, and art and epistemological, theoretical, and methodological assumptions supported by researchers involved with that trend. Finally, I indicate that research on/of/with daily life problematizes the historically constructed purity of scientific, philosophical, and artistic languages, overflowing agreed frontiers between the three modes of thinking about the world.